(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The urgency of the problems of forming an effective national policy for Russia remains. The article analyzes the historical aspects of the formation of the Russian state national policy, its concept, constitutional and legal principles. The 1993 Constitution of the Russian Federation, adopted in its development of federal laws, were designed to provide legal, organizational and material foundations of state national policy, the formation and dissemination of ideas of spiritual unity, preservation of historical heritage, further development of national identity and traditions of all peoples of Russia. However, not all problems were solved. Often, ethnic differences are the result of other unresolved problems in a state or a specific national or territorial community. The author considers the new version of the State National Policy Strategy, its the content is examined in systemic connection with the 1993 Constitution of the Russian Federation and other acts in the sphere of national relations. The new version of the Strategy, taking most of the problems and topical aspects of its implementation in practice, is focused on overcoming crisis phenomena in the sphere of national relations, creating comfortable living conditions for all Russian ethnic groups, and consistently carrying out constitutional standards for inter-ethnic interaction. The advantages of the new version of the Strategy, as well as gaps and disadvantages of legal regulation are revealed.